Biological effects of Physalis peruviana L. (Solanaceae) crude extracts and its major withanolides on Ceratitis capitata Wiedemann (Diptera: Tephritidae) - Cirigliano, A.=700 1 Colomarino, I.; Mareggiani, G.; Bado, S.
(Es, En)
Ilus., 16 ref.
Keywords: PHYSALIS PERUVIANA; SOLANACEAE; METABOLITOS; EXTRACTOS VEGETALES; INSECTICIDAS DE ORIGEN VEGETAL; CERATITIS CAPITATA; MORTALIDADA; ESPAÑA; ALTERACIONES EN DESARROLLO; BOLETIN DE SANIDAD VEGETAL: PLAGAS